Dissolution Kinetics of Columbite in Nitric Acid - S. Ayanda, Olushola; A. Adekola, Folahan; S. Fatoki, Olalekan (Asian Journal of Chemistry, 2011)
An investigation of the dissolution kinetics of a Nigerian columbite mineral ore sample in nitric acid media has been undertaken. The effects of acid concentration, process temperature, stirring rate and particle size on the dissolution rate were also investigated. Experimental results indicated that columbite dissolution was greatly influenced by hydrogen ion concentration and the leaching data fitted a diffusion model. Values of 15.100 kJ mol-1 and 9.42 × 10-5 min-1 were obtained for the activation energy and Arrhenius constant of columbite dissolution in nitric acid respectively and the order of reaction was 0.35.